When simplifying power of a power expression, simply multiply the two powers.
Let's start with the first expression.
![(4^0)^(-9)=4^(0*-9)=4^0](https://img.qammunity.org/2023/formulas/mathematics/college/enp34ta9x4n607yrdi2h5sx4cbh6j7k9e1.png)
Hence, the first expression matched with 4⁰.
Moving on to the second expression,
![(-4^9)^2\Rightarrow(-4^)^(9*2)=(-4)^(18)](https://img.qammunity.org/2023/formulas/mathematics/college/grsrt0quxyh06ac6ky9cp6a41063wgi5oe.png)
Hence, the second expression match with (-4)¹⁸.
For the third expression,
![(4^6)^(-3)\Rightarrow4^(6*-3)=4^(-18)=(1)/(4^(18))](https://img.qammunity.org/2023/formulas/mathematics/college/bqaklvmloipnbpzraans4rj0vda8zopykp.png)
Hence, the third expression match with 1/4¹⁸.
Lastly, moving on to the 4th expression,
![(4^(-3))^(-3)\Rightarrow4^((-3*-3))=4^9](https://img.qammunity.org/2023/formulas/mathematics/college/9exmo84kgo090z0rc0kvc1qobxyhiy2ite.png)
Hence, the 4th expression match with 4⁹.